A deep neural network approach for intelligent crop selection and yield prediction based on 46 parameters for agricultural zone-28 in Bangladesh - Islam, Tanhim; Chisty, Tanjir Alam; Roy, Prova (BRAC University, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.